The new polymath : profiles in compound-technology innovations - Mirchandani, Vinnie (Hoboken, N.J. : John Wiley & Sons, 2010)
Prepare for a world of compound innovation which blends 3, 5, 10 strands of infotech, greentech, biotech and healthtech to solve the "Grand Challenges" our world faces-and the more routine ones. Polymath is the Greek word for a Renaissance person like Leonardo Da Vinci or Ben Franklin who excels in many disciplines. The New Polymath is an enterprise which has learned to amalgamate 3, 5, 10 strands of technology-infotech, cleantech, healthtech, nanotech, biotech-to create compound new products and to innovate internal processes. Anchors around case studies on innovations and creative
Prologue: The field of polymath dreams -- The new polymath : in an age of "wicked problems" and technology abundance -- Modern-day dark ages : so much stagnation -- Polymath profile #1 : General Electric -- Residence : better technologically equipped than the office -- Exotics : innovation from left field -- Polymath profile #2 : Cognizant -- Networks : bluetooth to broadband -- Polymath profile #3 : Plantronics -- Arsonists : and other disruptors -- Polymath profile #4 : W.R. Hambrecht -- Interfaces : for all our senses -- Sustainability : delivering to both the green and gold agendas -- Polymath profile #5 : Kleiner Perkins Cleantech -- Singularity : human-machine convergence -- Analytics : spreadsheets, search, and semantics -- Polymath profile #6 : National Hurricane Center -- Networks again : communities, crowds, contracts, and collaboration -- Clouds : technology-as-a-service -- Polymath profile #7 : salesforce.com -- Ethics : in an age of cyberwar and cloning -- Polymath profile #8 : BP CTO -- Moon shots for budding polymaths -- Epilogue: The beginner's mind.
Includes bibliographical references (pages 307-323) and index.
Print version record.
John Wiley and Sons
Keywords: Technological innovations; Innovations; BUSINESS & ECONOMICS -- Structural Adjustment; Technological innovations; Case studies; Case studies; 2